Penerapan Etika Bisnis Islam Dalam Transaksi Jual Beli Di Pasar Tradisional: Studi Pasar Sungai Bengkal - Siti Aisah; Suhar Suhar; Saijun Saijun (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This study has a formulation of the problem regarding how to apply Islamic business ethics in buying and selling transactions in traditional markets Sungai Bengkal Market and how to apply Islamic business ethics in buying and selling transactions in traditional markets in Sungai Bengkal Village based on the principles of Rasulullah Saw. This study uses qualitative methods, the type of data used in this study is primary data and data collection techniques are through observation, interviews and documentation so that the results of this study indicate that the application of Islamic business ethics has been going quite well. It is proven by the way traders carry out buying and selling transactions following the principles of Rasulullah SAW such as being honest, trustworthy, precise in weighing, not hoarding goods, not doing al-ghab/tadlis and mutual benefit. Most of them have implemented it even though they don't know that it is included in Islamic business ethics. This is caused by a lack of knowledge about Islamic business ethics and some of the traders also only have elementary and high school graduates.